(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
Problem-solving behavior through a new responses chain happens when, facing a problem situation, a new response occurs resulted from the chaining of two or more independently learned answers. Objective: to evaluate the influence of ayahuasca in this process. Methodology: 12 male wistar rats were divided into groups: chronic, acute and control. The design was divided into: 1) habituation, 2) pre-test (open field/problem-solving), 3) training of the responses, 4) post-test (open field/ problem-solving). The substance was administered via gavage (2 ml/kg) to animals in the chronic group from phase 4 to 6, and in the acute group on stages 5 and 6. Animals in the control group ingested water. Results: There was no influence on problem-solving behavior, but there was in the training fase, which was slower for the chronic group. In the open field, there was a decrease in locomotor and exploratory activity in animals under the effect of ayahuasca.